Diagnóstico da competitividade dos fornecedores de revestimento automotivo - Demarchi, Valquíria (2009)
One of the major challenges for the automotive industry companies’ is to keep competitiveness. This study approaches the evolution of the textile industries section competitiveness in the long run destined to supply materials for automotive industry. The objective of the research is verify the topics that interfere with the create value of the process of materials supply to the competitive of long term. Thus, it is prominent to study the main factors of covering that impact in supplying Brazilian automotive industries output. The bibliographical review approaches the competitiveness, productivity and adopted strategies. In order to better explore this matter, it was accomplished an applied, exploratory and descriptive, through inductive approach, and qualitative research in according with the boarding of the problem. Study case was the technical procedure; the data collection was carried out through questionnaires. Identify the situation of the implantation of supplier’s innovation tools approach and identify how the organizations plan your strategy to supply of short, medium and long term. It was realized that the factors considered in competitiveness, inclusion of these companies in clusters and revision of the organizational structure are recommended as start points to be considered.